Patterns of Voluntary Participation in Membership Associations: A Study of UK Heritage Supporter Groups - Holmes, Kirsten; Slater, A. (Sage Publications, Inc., 2012)
Previous studies of membership associations identify differences between passive and active participation and also identify both sociodemographic and motivational factors as influencing participation. Extant research has, however, relied on cross-sectional survey data which does not capture the whole picture of an individual’s memberships. This article reports on a mixed-methods study of members of voluntary associations in the UK heritage sector to examine patterns of participation. The data reveals intensity of participation ranging from passive to active membership and we identify a new form of engagement: substituters. We find motivation to be the main influence on participation level and identify a new group of members based on their motivation: hobbyists. The data also reveals barriers to participation, including distance to the heritage site, aging, work and family commitments, and participation in other membership or voluntary associations. Last, members display varying levels of participation over time within the same association.